Determinant of Taxpayer’s Behavioral Intention to Use ESystem in Taxation - Surmayanti, Reni; Sudarma, Made; Roekhudin, Roekhudin (Jurnal Reviu Akuntansi dan Keuangan)
Determinant of Taxpayer’s Behavioral Intention to Use ESystem in Taxation. The purpose ofthis research is to examine the effect of attitude, subjective norms, perceived behavior control,perceived usefulness, perceived ease of use, self-efficacy and amount of information towardstaxpayer’s behavioral intention to use e-system in taxation. This research was conducted in KPPPratama Kuala Tungkal. Data collection method used is survey method by spreading the questionnaire. The sample of research is Personal Taxpayer (WPOP) who use e-system. Data analysis using Partial Least Square (PLS) with warpPLS software version 3.0. This research foundthatattitude, subjective norms and perceived behavior control does not affect the taxpayer’sbehavioral intention to use e-system in taxation. Perceived usefulness, perceived ease of use,self-efficacy and amount of information affects the taxpayer’s behavioral intention to use esystem in taxation.Keywords: Behavioral intention, e-system, Personal Taxpayer (WPOP).